The Influence of Self-Confidence, Motivation, and Commitment on Female Leadership in East Lombok: A Perspective of Educational Management - Murcahyanto, Hary (Sumber Belajar Sejahtera, 2025)
This study aims to analyze the influence of self-confidence, motivation, and commitment on female leadership in the Selong District of East Lombok. The research method employed is a descriptive quantitative approach using ex post facto design. The sample consisted of 100 female leaders in East Lombok, selected using Purposive Sampling. Data were collected through a questionnaire utilizing a Likert scale of 1-5. The results of the multiple linear regression analysis show that commitment has the most dominant influence on the quality of female leadership, with a beta coefficient of 0.188. Motivation also has a significant influence with a beta coefficient of 0.56, while self-confidence has a positive influence, though its beta coefficient is smaller (0.008). The partial test using the t-test revealed that all three factors significantly affect female leadership, with significance values for each factor less than 0.05. Simultaneously, these three factors explain 56.7% of the variation in the quality of female leadership, indicating that the combination of self-confidence, motivation, and commitment significantly contributes to leadership capabilities. This study provides implications for the development of leadership education and training programs focused on enhancing these three factors as part of empowering women in rural areas.